The effect of accounting disclosure in the efficient performance of the tax authority: Applied research in the General Commission for Taxes (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Starting with a problem of the weakness of accounting disclosure in some companies administration when preparing and presenting the financial reports which are submitted to the Tax authority. This problem impacts on Tax authority performance (The effect on the quality of the performance of the tax authority), because of the lack of conviction for the information contained in those reports, and the  failure to achieve accurate results in tax authority performance that leads to a negative impact on determining taxable income and affect tax revenue, as well as negative impact on  determining taxable income and affect tax revenue, as well as negative impact on the enhance of the profession of control and auditing. The importance of the research comes from dealing with the issue of accounting disclosure by corporate departments as a starting point for increasing tax revenues, as well as addressing accounting disclosure and its reflection in financial reports. The Finding of the study indicate that: There is a lack of accounting disclosure in some corporate departments when preparing and presenting financial reports submitted  to the tax authority, which affects the performance of the tax administration (affecting the quality of the tax  administrations  performance) because of the lack of satisfaction with the information contained in these reports, Achieve accurate results in the performance of tax administration  that lead to a negative impact on the determination of taxable income, and affect the tax revenue. As well as their negative, affect supporting the profession of auditing and auditing.Key recommendations are as follows:Strengthen the accounting disclosure in the preparation and presentation of the financial statements submitted to the tax authority by the auditor to ensure the positive impact on the performance of the tax administration (and influence the quality of the tax administrations performance) and to create the satisfaction of the information contained in those reports.